2020
DOI: 10.1177/0284185120938371
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference levels for fluoroscopically guided procedures in a South African tertiary hospital

Abstract: Background The burgeoning usage and complexity of fluoroscopically guided procedures (FGPs) contribute to extended examination times and increased risk of adverse radiation effects. Diagnostic reference levels (DRLs) play a pivotal role in dose optimization. There are limited DRL data for FGPs in low- and middle-income countries (LMICs). Purpose To determine local DRLs (LDRLs) for common FGPs in the South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The study identified the current scope of IR procedures carried out at a single institution while simultaneously determining procedures not performed or those performed with low frequency. Hepatobiliary (liver and pancreas) IR has room for growth through adding procedures such as TIPS, portal vein embolisation, transarterial chemo-embolisation (TACE), radio-embolisation with radioactive microspheres and radiofrequency ablation, a similar outcome to what another local study 13 at a public sector hospital found. This reflects the limited IR expertise in public sector hospitals and should improve with time as more radiologists and registrars are trained in IR.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The study identified the current scope of IR procedures carried out at a single institution while simultaneously determining procedures not performed or those performed with low frequency. Hepatobiliary (liver and pancreas) IR has room for growth through adding procedures such as TIPS, portal vein embolisation, transarterial chemo-embolisation (TACE), radio-embolisation with radioactive microspheres and radiofrequency ablation, a similar outcome to what another local study 13 at a public sector hospital found. This reflects the limited IR expertise in public sector hospitals and should improve with time as more radiologists and registrars are trained in IR.…”
Section: Discussionmentioning
confidence: 69%
“…Uterine artery embolisation recorded the highest DAP doses (selective abdominal vessel interventional angiogram was the second highest), in keeping with findings from other studies. Based on published literature, abdominal and pelvic angiographic interventions 13 , 17 typically have the highest recorded DAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon completion of the measurements, the KAP readings were corrected with the k KM TP measured using Accu-Gold 2.0 software. Finally, k KM Q,Q 0 were obtained as a function of the combination of the tube potential and spectral filter using Equation (8).…”
Section: Evaluation Of K Kmmentioning
confidence: 99%
“…6 KAP and K a,i values are generally used to estimate the individual patient doses or establish diagnostic reference levels that are commonly defined as a percentile of KAP and K a,i distributions for specific types of procedures in a specific region within a country. 7,8 Therefore, it is imperative to obtain the accurate KAP and K a,i values, and the measurement uncertainty for the KAP meter must be within ±35%. 5,9,10 The coronary arteries run along the surface of the heart, which is surrounded by the lungs.…”
Section: Introductionmentioning
confidence: 99%